Association between Maternal Serum Lipids and Intrapartum Oxytocin Requirements during Labor Induction and Augmentation - Frolova, Antonina I.; Prifti, Kevin K.; Raghuraman, Nandini; Carter, Ebony B.; England, Sarah K.; Stout, Molly J. (American Journal of Perinatology, 2022)
Objective This study aimed to investigate the relationship between maternal serum lipid parameters and oxytocin requirements among women with term vaginal deliveries.Study Design In this secondary analysis of a prospective cohort study, women who presented for delivery at ≥37 weeks' gestation and received oxytocin during their labor were included. Maternal serum was collected intrapartum. The cohort was stratified into two groups based on maximum oxytocin infusion dose during labor. Primary outcomes were maternal total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglyceride levels. Generalized linear regression models were used to assess the association between lipid parameters and maximum oxytocin dose requirements while controlling for potential confounders. For secondary analyses, the cohort was stratified by HDL-C into two groups. Multivariable logistic regression was used to evaluate the relationship between low maternal HDL-C and additional intrapartum oxytocin parameters.Results There were no differences in maternal total cholesterol, LDL-C, or triglyceride values between high and low maximum oxytocin groups. Median serum HDL-C was significantly lower among women in the high oxytocin group compared with those in the low oxytocin group (56 vs. 62 mg/dL, p < 0.01). For every 0.26 mg/dL lower HDL-C, women had 1 mU/min higher maximum oxytocin infusion dose during labor. Women with low serum HDL-C were also more likely to require maximum oxytocin doses above the 75th percentile (adjusted odds ratio [aOR]: 1.99, 95% confidence interval [CI]: 1.06–3.75) and above the 90th percentile (aOR: 2.47, 95% CI: 1.10–5.54). Among women undergoing induction of labor, low serum HDL-C was also associated with longer duration of oxytocin infusion (aOR: 2.07, 95% CI: 1.02–4.20).Conclusion Low maternal HDL-C levels at term are associated with higher maximum oxytocin infusion doses among women undergoing labor induction or augmentation. Given the growing prevalence of metabolic syndrome in the United States and persistently high rates of cesarean delivery, HDL-C or its components may present a new target for predicting and improving labor outcomes.Key Points
Keywords: labor; lipids; oxytocin; lipoprotein; uterine contractility